Design a highly specific sequence for electrochemical evaluation of meat adulteration in cooked sausages - Mansouri, Maryam; Khalilzadeh, Balal; Barzegari, AboulfazI; Shoeibi, Shahram; Isildak, Selim; Bargahi, Nasrin; Omidi, Yadollah; Dastmalchi, Siavoush; Rashidi, Mohammad-Reza (ELSEVIER ADVANCED TECHNOLOGY, 2020)
A specific and unique sequence probe was designed for detection of donkey adulteration in cooked sausages and its species specificity was confirmed bioinformatically in the common software and website (ClustalX and NCBI). Subsequently, a novel species-specific electrochemical DNA probe (locked nucleic acid, LNA) was synthesized and implemented in a construction of DNA-based electrochemical genosensor for sensitive, convenient and selective detection of donkey adulteration. The electrochemical behavior of the fabricated genosensor was studied by linear sweep, square wave, differential pulse voltammetry and electrochemical impedance spectroscopy techniques. Due to inherent optimal hybridization conditions, the lower limit of quantification (LLOQ) was obtained as 148 pM with a relative standard deviation of 0.16%. Eventually, as a proof of concept, the designed biosensor was successfully used for detection of donkey genetic element in consumable beef sausages preparations, as a real sample. It is predicted that the proposed biosensor will provide a sensitive, inexpensive, fast, and reliable bioassay for application in food analysis, forensic investigations, genetic screening and biodiagnostics. As a prominent feature of this study, the recorded results were confirmed by quantitative real time-polymerase chain reaction (QRT-PCR) as a standard method in adulteration analysis. Our future perspective is minutralization of the development bioassay for making on-desk device and specially merging the designed system by microfluidic systems for accelerating the analysis time.
Keywords: Electrochemistry; Adulteration; Sausage; Genosensor; LNA; Food analysis; NUCLEIC-ACID; PCR ANALYSIS; IDENTIFICATION; DNA; PORK; QUANTIFICATION; BEEF; FOOD; HEAT; Biophysics; Biotechnology & Applied Microbiology; Chemistry; Science & Technology - Other Topics